Kajian Vaksin Avian Influesa (AI) pada Ayam Buras dengan Sistem Kandang Kurung di Gunung Kidul Yogyakarta - W. Suwito; Supriadi Supriadi; E. Winarti; R. A. Primatika (Universitas Sebelas Maret (UNS), 2013)
Avian influenza (AI) is highly pathogenic desease in local chicken. Avian influenza (AI)vaccine is one of choice to prevent AI desease. The purpose of these study was to determine the effectiveness of AI vaccine in local chicken at the enclosure cage system in Gunung Kidul, Yogyakarta. A total of 110 local chicken consist of 100 hen and 10 cock were used in these study. The chicken was stored in cage of bamboo that have a measurement of 5 x 4 m2 include 10 hen and 1 cock in cage respectively. The vaccine used in these study was 2 kinds of commercial AI vaccine (A) and local AI vaccine (B). Vaccine with 0.5 ml dose was administrated by intramuscular (i.m) in 55 local chicken respectively. Re-vaccination was administrated after 2 month first vaccination. Examination of antibody titer AI was performed at month 2, 3, 4, 5 and 6 with chicken blood sampling collection via the brachial vein in the wing. Avian influenza vaccine commercial A and local B were protective in local chicken with enclosure cage system after 2 month vaccination and followed by booster.Key words: Avian influenza (AI), vaccine, local chicken